Combined high‐intensity local treatment and systemic therapy in metastatic head and neck squamous cell carcinoma: An analysis of the National Cancer Data Base. Issue 23 (17th August 2017) - Zumsteg, Zachary S.; Luu, Michael; Yoshida, Emi J.; Kim, Sungjin; Tighiouart, Mourad; David, John M.; Shiao, Stephen L.; Mita, Alain C.; Scher, Kevin S.; Sherman, Eric J.; Lee, Nancy Y.; Ho, Allen S.
Abstract : BACKGROUND: There is increasing evidence that primary tumor ablation can improve survival for some cancer patients with distant metastases. This may be particularly applicable to head and neck squamous cell carcinoma (HNSCC) because of its tropism for locoregional progression. METHODS: This study included patients with metastatic HNSCC undergoing systemic therapy identified in the National Cancer Data Base. High‐intensity local treatment was defined as radiation doses ≥ 60 Gy or oncologic resection of the primary tumor. Multivariate Cox regression, propensity score matching, landmark analysis, and subgroup analysis were performed to account for imbalances in covariates, including adjustments for the number and location of metastatic sites in the subset of patients with this information available. RESULTS: In all, 3269 patients were included (median follow‐up, 51.5 months). Patients undergoing systemic therapy with local treatment had improved survival in comparison with patients receiving systemic therapy alone in propensity score–matched cohorts (2‐year overall survival, 34.2% vs 20.6%; P < .001). Improved survival was associated only with patients receiving high‐intensity local treatment, whereas those receiving lower‐intensity local treatment had survival similar to that of patients receiving systemic therapy without local treatment. The impact of high‐intensity local therapy was time‐dependent, with a stronger impact within the first 6 months after the diagnosis (adjusted hazard ratio [AHR], 0.255; 95% confidence interval [CI], 0.210‐0.309; P < .001) in comparison with more than 6 months after the diagnosis (AHR, 0.622; 95% CI, 0.561‐0.689; P < .001) in the multivariate analysis. A benefit was seen in all subgroups, in landmark analyses of 1‐, 2‐, and 3‐year survivors, and when adjusting for the number and location of metastatic sites. CONCLUSIONS: Aggressive local treatment warrants prospective evaluation for select patients with metastatic HNSCC. Cancer 2017;123:4583‐4593 . © 2017 American Cancer Society . Abstract : High‐intensity local treatment, consisting of radiation doses of at least 60 Gy or oncologic surgery, is associated with improved survival for patients presenting with metastatic head and neck cancer and undergoing systemic therapy in comparison with lower intensity or no local treatment. This effect persists in propensity score–matched cohorts, in landmark analyses, and with adjustments for the number and location of metastatic sites.